Otitis Media with Effusion in Children and the Impact of Risk Factors on Serum Cytokine Levels - Arshi, Saba (Iran J Otorhinolaryngol, 2017)
INTRODUCTION: To evaluate the role of allergic-type and infectious-type cytokines in children with chronic otitis media with effusion (OME) MATERIALS AND METHODS: We investigated serum levels of interleukins (IL)-4, IL-5, and IL-13, along with interferon-gamma (IFN-γ) and tumor necrosis factor-alpha (TNF-α), by enzyme-linked immunosorbent assay (ELISA) in 35 children with OME and 28 healthy controls. RESULTS: Children with OME had significantly higher levels of IL-5 in comparison with the control group, ranging from 1 pg/ml in cases to 0.04 pg/ml in controls (P=0.009). However, after adjusting for confounding variables, there was no significant difference in serum levels of IL-13, IL-4, IFN-γ, or TNF-α between the two groups (P=0.287, P=0.627, P=0.793, and P=0.217, respectively) CONCLUSIONS: The findings of this study suggest that in comparison with the control group, serum IL-5 levels were elevated in OME cases.